2023
DOI: 10.1002/anie.202311559
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Broad Absorption Band with Small Singlet‐Triplet Energy Gap in Organic Photovoltaics

Baobing Fan,
Wei Gao,
Rui Zhang
et al.

Abstract: Organic photovoltaics (OPV) are one of the most effective ways to harvest renewable solar energy, with the power conversion efficiency (PCE) of the devices soaring above 19 % when processed with halogenated solvents. The superior photocurrent of OPV over other emerging photovoltaics offers more opportunities to further improve the efficiency. Tailoring the absorption band of photoactive materials is an effective way to further enhance OPV photocurrent. However, the field has mostly been focusing on improving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Our group further developed a series of NFAs with varied side-group conjugation length. An enhanced SWR absorption is observed for acceptor NFA26 with extended conjugated side-group, i.e., thieno­[3,2- b ]­thiophene . Meanwhile, we found that the enhanced SWR absorption is accompanied by a reduced singlet–triplet energy gap (Δ E ST ).…”
Section: Biaxially Conjugated Non-fullerene Acceptorsmentioning
confidence: 75%
See 4 more Smart Citations
“…Our group further developed a series of NFAs with varied side-group conjugation length. An enhanced SWR absorption is observed for acceptor NFA26 with extended conjugated side-group, i.e., thieno­[3,2- b ]­thiophene . Meanwhile, we found that the enhanced SWR absorption is accompanied by a reduced singlet–triplet energy gap (Δ E ST ).…”
Section: Biaxially Conjugated Non-fullerene Acceptorsmentioning
confidence: 75%
“…An enhanced SWR absorption is observed for acceptor NFA26 with extended conjugated side-group, i.e., thieno [3,2-b]thiophene. 97 Meanwhile, we found that the enhanced SWR absorption is accompanied by a reduced singlet−triplet energy gap (ΔE ST ). The enhanced SWR absorption leads to higher J SC of relevant OSCs, and the reduced ΔE ST is possibly related to the mitigated nonradiative recombination loss.…”
Section: Extension Of Side-group Conjugationmentioning
confidence: 98%
See 3 more Smart Citations